(Neo-)fascisms and the “fabrication of negative alterities”: contributions to the updating of the constitutional prohibition of fascist organisations in light of the structuring principles of the Portuguese legal system - Silva, Ricardo (UNIO – EU Law Journal, 2024)
This article will aim to explore the new far-right movements following the prohibition of organisations that follow the fascist ideology that the Portuguese Constitution outlaws, based on a characteristic that we will argue is common to the far-right and, a fortiori, to fascisms throughout their existence. That is the discrimination and persecution of people belonging to social groups with a history of oppression due to characteristics that make up their identities – we will call them identity minorities. First of all, we will try to analyse the relationship between the new far-right movements and the classical fascisms, to which the aforementioned prohibition is mainly associated. Having established this connection, we will seek to base our point of view on the incompatibility between the contemporary far-right and the founding principles of the Portuguese legal system and of the process of European integration, not ignoring, with the support of the works of Jorge Reis Novais, Charles Taylor, Emmanuel Levinas and Paul Ricœur, the demand for respect for the otherness of the Other that guides those two political and legal projects.